Access to Healthcare Services for Cardiovascular Diseases in Bomet County, Kenya - Kipkemoi, Rotich John; Odek, Antony; Wanjugu, Wachira (International Journal of Health Sciences, 2024)
Purpose: This study investigates the accessibility of healthcare services for cardiovascular diseases (CVDs) in Bomet County, Kenya, with a specific focus on the relationship between access and economic well-being among households. The research aims to identify key barriers to CVD care, assess the socioeconomic impacts of these diseases on affected families, and explore potential interventions to improve healthcare access and outcomes in rural Kenya. Methodology: A descriptive design study employing a mixed-methods approach, combining quantitative and qualitative data collection and analysis. A stratified random sample of 399 households from three sub-counties in Bomet County was surveyed using structured questionnaires. Additionally, 30 in-depth interviews were conducted with CVD patients and caregivers, along with three focus group discussions involving healthcare workers. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data underwent thematic analysis to identify recurring patterns and themes. Findings: The study reveals significant challenges in accessing CVD healthcare services in Bomet County, with only 23.2% of respondents reporting easy access. Financial constraints emerged as the primary barrier, cited by 75.2% of participants. CVD-affected households experienced substantial economic hardship, with healthcare expenditures consuming an average of 42% of non-food household income, compared to 12% for non-CVD households. The study also found that 68% of CVD-affected households faced catastrophic health expenditures. Qualitative data highlighted the emotional and social toll of CVDs on patients and their families, including asset depletion, increased debt, and food insecurity. Unique Contribution to Theory, Policy and Practice: This research enhances theoretical frameworks on health equity and access in resource-limited settings by providing a comprehensive analysis of the interplay between CVD care access, socioeconomic factors, and health outcomes in rural Kenya. The study's implications span policy and practice, advocating for the expansion of universal health coverage to include CVD services, implementation of financial protection mechanisms, and development of community-based care models. Practical recommendations include enhancing CVD screening programs, improving coordination between primary and specialized care, implementing telemedicine solutions, and developing support systems for CVD patients and their families. These insights contribute to both the academic discourse on health disparities and provide actionable strategies for improving CVD care in similar resource-constrained environments.